The Fog of Peace : A Memoir of International Peacekeeping in the 21st Century - Guehenno, Jean-Marie, 1949- (Book collections on Project MUSE., 2015)
For more than a decade, international peacekeeping forces have been engaged in Afghanistan, the Democratic Republic of Congo, and Sudan - yet peace is far from secured. Meanwhile, a skeptical observer is left wondering if anything can be accomplished by costly interventions in faraway lands, especially as fear of more immediate threats - most acutely in the form of terrorist acts orchestrated by individuals or small groups - loom in the streets of New York, London, Paris, and other major cities. Guehenno draws on his experience as the head of the United Nations Department of Peacekeeping Operations from 2000 to 2008, a period that included intense negotiations and spiraling crises in Afghanistan, Iraq, and Sudan, to reflect on some of the most difficult questions facing international interventions today.